Dentate total molecular layer interneurons mediate cannabinoid‐sensitive inhibition. Issue 8 (9th February 2015) - Yu, Jiandong; Swietek, Bogumila; Proddutur, Archana; Santhakumar, Vijayalakshmi
ABSTRACT Activity of the dentate gyrus, which gates information flow to the hippocampus, is under tight inhibitory regulation by interneurons with distinctive axonal projections, intrinsic and synaptic characteristics and neurochemical identities. Total molecular layer cells (TML‐Cs), a class of morphologically distinct GABAergic neurons with axonal projections across the molecular layer, are among the most frequent interneuronal type in the dentate subgranular region. However, little is known about their synaptic and neurochemical properties. We demonstrate that synapses from morphologically identified TML‐Cs to dentate interneurons are characterized by low release probability, facilitating short‐term dynamics and asynchronous release. TML‐Cs consistently show somatic and axonal labeling for the cannabinoid receptor type 1 (CB1R) yet fail to express cholecystokinin (CCK) indicating their distinctive neurochemical identity. In paired recordings, the release probability at synapses between TML‐Cs was increased by the CB1R antagonist AM251, demonstrating baseline endocannabinoid regulation of TML‐C synapses. Apart from defining the synaptic and neurochemical features of TML‐Cs, our findings reveal the morphological identity of a class of dentate CB1R‐positive neurons that do not express CCK. Our findings indicate that TML‐Cs can mediate cannabinoid sensitive feed‐forward and feedback inhibition of dentate perforant path inputs. © 2015 The Authors Hippocampus Published by Wiley Periodicals, Inc.